PERANCANGAN MEDIA PENGENALAN HURUF HIJAIYAH BERBASIS MULTIMEDIA PADA TK PUSAT PADU KARTINI DESA BUKIT HARAPAN - Wira, Wira; Farida, Farida; Faizah, Andi Nurul (CV. LAJAGOE PUSTAKA, 2024)
This research aims to : (1) designing media in learning to recognize hijaiyah letters in children,(2) implementing hijaiyah letter recognition learning applications in children.The research method in designing this multimedia based hijaiyah letter recognition learning media uses the multimedia version Luther-Sutopo that is Multimedia Development Life Cycle (MDLC) dengan tahap Concept, Design, Material Collecting, Assembly, dan Testing dengan menggunakan Black Box.of the development. As for the method of collecting date in research with the stages of observation, literature study, interviews, questionnaires, and documentation.The result of this research is (1) The design stage of learning media for introducing hijaiyah letters to students in class A,class B1,class B2, kindergarten at padu kartini village, designed using the method development, namely the multimedia development life cycle (MDLC). This research aims to develop a more interesting and efficient learning so that it namely with the input design stage, namely Unified Modeling Language (UML), namely, use case diagrams, activity diagrams, sequence diagrams and statechart diagrams as well as output design using macromedia flash 8 software. (2) This hijaiyah letter recognition learning media has been implemented for students in class a, class b1, class b2 kindergarten center pusat padu kartini desa bukit harapan village which can be used in the learning process as a new learning medium and has been validated with the results of blacbox testing and all buttons or icons. running according to function.